El uso de los sujetos pronominales explícitos y nulos por los aprendices de ELE - Bran, Rǎzvan (Acta Hispanica, 2015)
This paper aims to analyse the errors made by Romanian students who learn Spanish as a Foreign Language in using pronominal and null subjects. Neither Romanian (students´ L1) nor Spanish require pro subjects, but after investigating the corpus (including opinion essays and narratives), we have noticed that pronominal subjects are misused. In our view, one possible explanation of this syntactic error could be the interference with other foreign languages that students learn, which are pro-drop languages. This type of error appears more often in the first stage of interlingua and the more advanced the student is, the less errors he makes. As the syntactic competence is fundamental in the acquisition process of the L2, it is very important this phenomenon to be reckoned both by students and by teachers.